An investigation into some of the organic constituents of soft and hard tissues of the body - Solomons, C.C. (My University, 1957)
The roles played by fibrous proteins in nature are at present being intensively studied and some of the advances in our knowledge of these proteins are the subject of several recent symposia. (la,b) The powerful techniques of X-ray diffraction end electron— optic analysis as well as ran unprecendented improvement in the specificity and accuracy of chemical and chromatographic methods of analysis has led to ever increasing efforts to interpret biological phenomena within a framework of physicochemical principles. In many fields, particularly those of virus research and muscle contraction these efforts have already been rewarded by a large measure of success. In the present work, which forms part of a program of research into the chemistry of connective tissues of man and other vertebrates, the chemical properties and structural features of the extracellular collagenous proteins in some calcified and uncalcified connective tissues are compared. 'In vivo' calcification of connective tissue is generally thought to be the result of a physico-chemical combination between lima salt3 and the organic matrix mediated by the ionic and structural prop rties of the matrix and the activity of various cello and enzymes
Submitted in fulfilment of the requirements for the degree of Ph.D in the F culty of Science, University of the Witwatersrand, Johannesburg. February 1957.
Keywords: Biochemistry; Tissues anatomy & Histology; Scleroproteins